2010
DOI: 10.1258/la.2010.009114
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain in response to high-fat feeding in CD-1 male mice

Abstract: The purpose of this study was to compare weight gain and food intake during high-fat feeding in outbred CD-1 male mice while considering several different experimental designs. This study was completed using data from three separate experiments and was designed to address different experimental design issues. Experiment 1 compared mice housed in groups or singly. Experiment 2 compared adolescent and young adult mice. Experiment 3 examined mice that had been previously exercise-trained prior to diet-induced wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
2
20
1
1
Order By: Relevance
“…We have previously demonstrated that mice that are group-housed (groups of five) and restricted from structured physical activity have greater weight gain than normal growth rates. 10,11 Consistent with reports from other laboratories, we have also demonstrated that extremely high-fat diets (60% of calories from fat) result in excessive weight gain above normal growth. 10 Neither our laboratory nor others have specifically compartmentalized weight gain into lean and fat masses.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We have previously demonstrated that mice that are group-housed (groups of five) and restricted from structured physical activity have greater weight gain than normal growth rates. 10,11 Consistent with reports from other laboratories, we have also demonstrated that extremely high-fat diets (60% of calories from fat) result in excessive weight gain above normal growth. 10 Neither our laboratory nor others have specifically compartmentalized weight gain into lean and fat masses.…”
supporting
confidence: 92%
“…10,11 Consistent with reports from other laboratories, we have also demonstrated that extremely high-fat diets (60% of calories from fat) result in excessive weight gain above normal growth. 10 Neither our laboratory nor others have specifically compartmentalized weight gain into lean and fat masses. The accounting of fat mass is important because this change, rather than body weight, underlies disease onset and progression.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…16 In order to complete the aims of the study, mice were randomly divided into one of three groups (n ¼ 12 per group): diet-induced weight gain, sedentary (DS), diet-induced weight gain, forced treadmill running (DE) and served as a control group. The fat source in both diets was soybean oil and lard (cholesterol content ¼ 0.95 mg/ g).…”
Section: Experimental Designmentioning
confidence: 99%
“…Obesity is one of the causes that lead to liver injury [8]. Nowadays, one of the main causes of obesity was developed from high intake of processed food or junk food, which contains high amounts of calories [9]. This kind of diet is predominant in the western world and is very popular among children in developing countries [10].…”
Section: Biochemical Analysismentioning
confidence: 99%